The determining role of health on the economic development of countries – case study in econometric analysis - Unsal, Ali; Kırılmaz, Harun; Stawicka, Ewa (Turystyka i Rozwój Regionalny, 2018)
Nowadays, the ultimate goal of all countries is to provide their citizens a higher quality of life and to build a prosperous society by carrying out the sustainable development. And these goals can be achieved only by investing in human capital. The method of investment in human capital goes through education services along with high-quality, reachable, inclusive and adequate health services. Development is not only an economic term. Development – in addition to economic growth (in addition to increase in per capita income) – includes improvement on economic, social, cultural and political form in a country. In this sense; health indicators such as maternal mortality rate, infant mortality rate and life expectancy at birth are being accepted to be the most primary criteria which determine the development level of countries. This study aims to reveal the role of health services on the development level of countries by making a comparative analysis between Turkey – which is a member of OECD and which presents in the league of developing countries – and selected developed OECD countries on indicators such as; infant mortality rate and GDP per capita.